2006
DOI: 10.1097/01.coc.0000195085.34162.88
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Number of CAG Repeats on Local Control in the RTOG 86-10 Protocol

Abstract: Patients with short CAG repeats show a local control benefit with short-term androgen deprivation therapy, but no improvement in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…In this study, we had the opportunity to evaluate VEGF levels in the well-characterized RTOG 8610 patient population. There have been a number of other biomarker studies done in this patient population already, and this study complements what is known for this patient population [45-51]. However, with the limitations presented, we acknowledge that this secondary analysis of RTOG 8610 will not serve to make the definitive statement regarding whether VEGF is a useful biomarker or not, but reporting on this well-characterized patient population with long-term follow-up and numerous other biomarker publications arising from this population is in our opinion a significant contribution to the current heterogeneous VEGF literature [18-28,31-34].…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we had the opportunity to evaluate VEGF levels in the well-characterized RTOG 8610 patient population. There have been a number of other biomarker studies done in this patient population already, and this study complements what is known for this patient population [45-51]. However, with the limitations presented, we acknowledge that this secondary analysis of RTOG 8610 will not serve to make the definitive statement regarding whether VEGF is a useful biomarker or not, but reporting on this well-characterized patient population with long-term follow-up and numerous other biomarker publications arising from this population is in our opinion a significant contribution to the current heterogeneous VEGF literature [18-28,31-34].…”
Section: Discussionsupporting
confidence: 54%
“…Although several studies have attempted to determine the role of AR -CAG repeat length on the outcomes of ADT, the results remain uncertain. Some studies showed that shorter CAG repeat length was correlated with better responses to hormonal therapy [30], [31], an observation consistent with the present study. On the other hand, other studies found that patients with better clinical responses to ADT had a longer CAG repeat length [32], [33], or in some cases, no correlation was found [34][37].…”
Section: Discussionsupporting
confidence: 92%
“…Pretreatment serum levels of testosterone or adrenal androgens were considered, but were modestly predictive of response to ADT [112][113][114][115]. At the molecular level, ADT response was associated with AR (variant) expression levels [116], length of AR CAG repeats that affect activity of AR [117,118], expression of steroidogenic enzymes targeted by ADT such as CYP17A1 [119], and germline polymorphisms in androgen transporters [120]. Expression status of two AR target genes, PSA and PSMA, in CaP circulating tumor cells, were used as a measure of AR activity and correlated with CaP response to ADT [121].…”
Section: Future Directionsmentioning
confidence: 99%